2021
DOI: 10.1155/2021/6135920
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Biogenic Silver Nanoparticles with Eco-Friendly Processes Using Ganoderma lucidum Extract and Evaluation of Their Theranostic Applications

Abstract: The green synthesis of silver nanoparticles (AgNPs) using plant extract, the cost-effective solution, and the abundance and environmental issue have been gaining much attention to scientists. Ganoderma lucidum (GL) commonly known as Lingzhi in Chinese and Reishi in Japanese, with a proven anticancer benefit, is discovered in the buffer zone of Bach Ma National Park, Nam Dong district, Thua Thien Hue province. In this work, the AgNPs were synthesized in a simple and effective biochemical reduction process using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 43 publications
2
22
2
Order By: Relevance
“…Synthesis of metallic NPs using G. sessile has not been previously reported; therefore, the optimized protocol used for T. harzianum was applied. A similar protocol was used to synthesize NPs using G. lucidum by [ 32 ], who reported AgNPs of 10.72 nm using the supernatant of fruiting bodies. The authors described as optimum conditions the use of 1 mM AgNO 3 and a reaction temperature of 85 °C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of metallic NPs using G. sessile has not been previously reported; therefore, the optimized protocol used for T. harzianum was applied. A similar protocol was used to synthesize NPs using G. lucidum by [ 32 ], who reported AgNPs of 10.72 nm using the supernatant of fruiting bodies. The authors described as optimum conditions the use of 1 mM AgNO 3 and a reaction temperature of 85 °C.…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies for the synthesis of AgNPs using Ganoderma spp. have been carried out with G. lucidum [ 32 , 42 , 43 , 45 , 46 , 47 ]. Strong bactericidal activity against S. aureus , E. coli , Staphylococcus mutants, Klebsilla pneumoniae and P. aeruginosa was reported using AgNPs (5–30 nm) synthesized with the supernatant of G. lucidum [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nguyen and colleagues [286] reported on the treatment of hepatocellular carcinoma (HepG2) and breast cancer (MCF-7) with AgNPs synthesized in the presence of Ganoderma lucidum (GL). Additionally, they demonstrated that spherical nanoparticles of AgNPs/GL with a physical size of 10.72 nm effectively inhibited the proliferation of HepG2 and MCF-7 cells.…”
Section: Agnps For Anticancer Therapymentioning
confidence: 99%
“…contain reducing and capping agents that are responsible for the synthesis of these Ag-NPs. 71 The list of different fungal species used to synthesize different nanoparticles have been comprehended in Table 1 .…”
Section: Edible and Medicinal Mushroomsmentioning
confidence: 99%